PEMBINAAN PEMANFAATAN LIMBAH BOTOL PLASTIK UNTUK MEDIA PEMBELAJARAN IPA INTERAKTIF - Kurnia, Dadang; Alfatiyah, Rini; Subarman, Karya; Mualif, M.; Dahniar, Tedi (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Untung Jawa Village, DKI Jakarta is one of the tourist destinations of both local and international tourists in the Administrative District of the Thousand Islands District. As a tourist attraction, Untung Jawa Island cannot be separated from the problem of garbage or waste, one of which is the waste is in the form of a plastic bottle for drinks. The Industrial Engineering Study Program, Pamulang University, in its Community Service activities, carries out the activities of utilizing plastic bottles to become science learning media or interactive science in the form of water rocket props. The water rocket props not only enhance the understanding of scientific phenomena related to Newton's Law but can also open up opportunities for students to take part in regional, national and international water rocket competitions. Untung Jawa Village Community, Untung Jawa residents of DKI Jakarta who participated in the program of developing plastic bottle waste utilization as many as 45 participants and gave positive responses to interactive science learning media as many as 30 participants (66%), interested in regional competitions 26 participants (58%), interested international competition 15 participants (33%), and interested in applying the science learning media + competition 9 participants (20%)Keywords: plastic bottle waste, science learning media, water rocket